Low pH Exposure During Immunoglobulin G Purification Methods Results in Aggregates That Avidly Bind Fcγ Receptors: Implications for Measuring Fc Dependent Antibody Functions - Lopez, Ester; Scott, Nichollas E.; Wines, Bruce D.; Hogarth, P. Mark; Wheatley, Adam K.; Kent, Stephen J.; Chung, Amy W. (Frontiers in Immunology, 2019)
Evaluating the biophysical and functional nature of IgG is key to defining correlates of protection in infectious disease, and autoimmunity research cohorts, as well as vaccine efficacy trials. These studies often require small quantities of IgG to be purified from plasma for downstream analysis with high throughput immunoaffinity formats which elute IgG at low-pH, such as Protein G and Protein A. Herein we sought to compare Protein G purification of IgG with an immunoaffinity method which elutes at physiological pH (Melon Gel). Critical factors impacting Fc functionality with the potential to significantly influence FcγR binding, such as IgG subclass distribution, N-glycosylation, aggregation, and IgG conformational changes were investigated and compared. We observed that transient exposure of IgG to the low-pH elution buffer, used during the Protein G purification process, artificially enhanced recognition of Fcγ Receptors (FcγRs) as demonstrated by Surface Plasmon Resonance (SPR), FcγR dimer ELISA, and a functional cell-based assay. Furthermore, low-pH exposed IgG caused conformational changes resulting in increased aggregation and hydrophobicity; factors likely to contribute to the observed enhanced interaction with FcγRs. These results highlight that methods employed to purify IgG can significantly alter FcγR-binding behavior and biological activity and suggest that the IgG purification approach selected may be a previously overlooked factor contributing to the poor reproducibility across current assays employed to evaluate Fc-mediated antibody effector functions.